Seasonal variations in photoperiod affect hepatic metabolism of medaka (Oryzias latipes). Issue 4 (28th February 2021) - Fujisawa, Koichi; Takami, Taro; Shintani, Haruko; Sasai, Nanami; Matsumoto, Toshihiko; Yamamoto, Naoki; Sakaida, Isao
Abstract : Organisms living in temperate regions are sensitive to seasonal variations in the environment; they are known to accumulate energy as fat in their livers during the winter when days are shorter, temperatures are lower, and food is scarce. However, the effect of variations in photoperiod alone on hepatic lipid metabolism has not been well studied. Therefore, in this study, we analyzed lipid metabolism in the liver of medaka, Oryzias latipes, while varying the length of days at constant temperature. Larger amounts of fatty acids accumulated in the liver after 14 days under short‐day conditions than under long‐day conditions. Metabolome analysis showed no accumulation of long‐chain unsaturated fatty acids, but showed a significant accumulation of long‐chain saturated fatty acids. Short‐day conditions induced a reduction in the levels of succinate, fumarate, and malate in the tricarboxylic acid cycle, decreased expression of PPARα, and decreased accumulation of acylcarnitine, which suggested inhibition of lipolysis. In addition, transparent medaka fed on a high‐fat diet under short‐day conditions exhibited greater amounts of fat accumulation and developed fatty liver. The findings of our study will be useful for creating a medaka hepatic steatosis model for future studies of hepatic steatosis‐related diseases. Abstract : In this study, we analyzed lipid metabolism in the liver of medaka, Oryzias latipes, while varying the length of days at constant temperature. Larger amounts of fatty acids accumulated in the liver after 14 days under short‐day conditions than under long‐day conditions. The findings of our study will be useful for creating a medaka hepatic steatosis model for future studies of hepatic steatosis‐related diseases.